2021
DOI: 10.1177/1362361320984315
|View full text |Cite
|
Sign up to set email alerts
|

Differential predictors of well-being versus mental health among parents of pre-schoolers with autism

Abstract: Extensive research has shown elevated mental health difficulties among parents of children with autism compared to other parents. Although several studies have explored factors related to mental health among parents of children with autism, the factors that influence and promote well-being remain poorly characterised. Parents of young, newly diagnosed autistic children may also be particularly vulnerable to stressors that impact mental health and well-being. We examined child-, parent-, and family/socioeconomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Indeed, there is a distinction between well-being and positive mental health (Kinderman et al, 2015;Salomone et al, 2018). In a recent study of mental health and well-being in parents of autistic preschoolers (Green et al, 2021), which shared participants with the current sample, parental well-being was predicted by parents' trait sociability and mindfulness, whereas parental mental health was predicted by trait negative emotionality of the parent and child autism symptoms. There is an indication that parental well-being may be more affected by internal factors (i.e.…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, there is a distinction between well-being and positive mental health (Kinderman et al, 2015;Salomone et al, 2018). In a recent study of mental health and well-being in parents of autistic preschoolers (Green et al, 2021), which shared participants with the current sample, parental well-being was predicted by parents' trait sociability and mindfulness, whereas parental mental health was predicted by trait negative emotionality of the parent and child autism symptoms. There is an indication that parental well-being may be more affected by internal factors (i.e.…”
Section: Discussionmentioning
confidence: 81%
“…Mothers were more invested in a shared parenthood relationship when parents felt more competent in raising their children. Green et al (2021), conducted a comprehensive study that found that parents of children with autism have greater mental health problems compared to other parents. Although several studies have examined factors related to the mental health of parents of children with autism, factors affecting and contributing to well-being remain poorly characterized.…”
Section: Pedagogical Science Has Never Abandoned This Term the More S...mentioning
confidence: 99%
“…In other words, this research will seek policy solutions that can lighten the burden of responsibility for parents with children with autism. Indeed, indicated that early diagnosis of childhood autism might help parents lead healthier lives when raising their children [6]. In other words, they would know more about the condition and how to look after the child.…”
Section: Introductionmentioning
confidence: 99%